The Impact Of Digital Content Marketing’s Informativeness And Entertainment On Brand Trust (A Study On The Customers Of Gojek Indonesia) - Muhammad Rizky Ramadhan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This research examined the impact of digital content marketing’s informativeness and entertainment on brand trust on the customers of Indonesian Unicorn, GOJEK. This research is descriptive research with both primary and secondary data of GOJEK Indonesia’s customers. This research used non-probability sampling to obtain all samples, and a total of 210 samples of GOJEK customers were collected. The result of this research showed: (1) Digital content marketing’s informativeness has a direct positive, and significant impact on customers’ brand trust; (2) Digital content marketing’s entertainment has a direct positive and significant influence on customers’ brand trust. In concluding, both dimensions of digital content marketing have a significant positive influence on brand trust. The results support previous studies that show the positive relationship between digital content marketing’s informativeness and entertainment and brand trust.Keywords: Digital Content Marketing, Informativeness, Entertainment, Brand Trust